Decomposition of n- and sec-Butyl Acetate on Synthetic Zeolites and Silica-Alumina - Imai, Tamotsu (My University, 1971)
A kinetic and mechanistic study on catalytic decomposition of n- and sec-butyl acetate was carried out. The catalysts were silica-alumina and synthetic zeolites including type A, X, Y and mordenite. The reactions were performed in the temperature region of 140° to 290°C at atmospheric pressure using a fixed-bed flow reactor.
The esters decomposed to acetic acid and n-butenes. The isomerization of butenes occurred consecutively. The mechanism of ester decomposition was different from that of pyrolysis. The catalytic activity was effected by acidity, cations and pore size. The Langmuir-Hinshelwood rate equation corresponding to the surface reaction on dual-sites correlated data satisfactorily. Strong adsorption of acetic acid, crystal collapse and the blocking of pores with organic deposit caused aging of catalysts.
Keywords: decomposition, Butyl, acetate, synthetic, zeolites, silica-alumina, reactions, organic, deposit, isomerization, temperature